Systematic Literature Review: Penggunaan Quiziz Pada Pembelajaran Matematika - Agustian, Dendi (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
Mathematics learning often presents challenges for students because of its abstract and complex nature. As technology develops, the use of quiz-based learning platforms such as Quizizz has become increasingly popular as a solution to enhance student engagement and motivation. This study aims to systematically review the effectiveness of using Quizizz in mathematics education through a Systematic Literature Review (SLR) approach. In this study, 16 accredited articles discussing the application of Quizizz in mathematics learning were analyzed. The analysis results show that using Quizizz can increase student motivation, facilitate understanding of the material, and improve mathematics learning outcomes. However, implementing Quizizz requires careful preparation, especially in designing questions that align with the learning objectives. This article also discusses the challenges in applying Quizizz, such as limited devices and adequate internet connectivity. This study provides practical recommendations for teachers to design more effective and enjoyable mathematics learning by utilizing the Quizizz platform.